The microbiomes of two Singaporean corals show site-specific differentiation and variability that correlates with the seasonal monsoons - Deignan, Lindsey Kane (2023)
Corals host abundant microbial communities, or microbiomes, that play essential roles in the function of the coral holobiont. We examined the mucus microbiome in corals within the port of Singapore, where corals persist despite intense anthropogenic impacts. The coral mucus microbiomes of Pectinia paeonia and Platygyra sinensis at three reef sites were tracked by 16S rRNA gene amplicon sequencing from January 2019 to January 2020. Both coral species displayed spatial and temporal differences in microbiome composition, suggesting site specificity and seasonality in microbiome composition consistent with the monsoons. The temporal shifts in relative abundance of dominant taxa were different between the two coral species. Nonetheless, Proteobacteria was the most abundant phylum in both coral species and was reduced during the southwest (SW) monsoon, while Cyanobacteria and Crenarchaeota increased. The presumptive beneficial endosymbiont Endozoicomonas was only associated with corals at the reef site located the farthest from the Singapore mainland. The coral microbiomes reflected seasonal changes, while the seawater displayed distinct temporal microbial compositions and site-specific differentiation within all sampling dates. The persistence of coral reefs within the port of Singapore highlights the adaptive ability of corals to respond to stressful environments, and this study provides further evidence that a flexible microbiome could be an important part of the strategy employed by corals to remain resilient.